Seizures and Anticonvulsants in Brain Tumours: Frequency, Mechanisms and Anti-Epileptic Management - Vecht, Charles; Royer-Perron, Louis; Houillier, Caroline; Huberfeld, Gilles (Current Pharmaceutical Design, 2017)
In cancer, epilepsy can be the manifestation of a primary brain tumour, metastatic disease, vascular or surgical complications, opportunistic infection or secondary to anti-tumour therapy. Seizures are frequently the first symptom of a brain tumour. The epilepsy is related to elevated extracellular glutamate stimulating NMDAand AMPA-receptors and to the formation of D-2HG which resembles glutamate in IDH1 mutated gliomas. Epilepsy as presenting sign is associated with a longer survival in low- and high- grade gliomas, particularly with the IDH1 mutation. Anti-tumour treatment by surgery, radiotherapy or chemotherapy strongly contributes to seizure control. Symptomatic management of brain tumour-related epilepsy (BTE) by evidenced-based anti-epileptic drugs (AEDs) as indicated for focal epilepsy depends on individual patient factors including age, sex, weight, co-morbidity and cotherapy. Levetiracetam followed by lacosamide or valproic acid are the agents of choice. Both can be combined with levetiracetam in case monotherapy is inactive or produces side-effects. Lamotrigine, perampanel, zonisamide or clobazam are other good choices. On seizure prophylaxis, there is some evidence for its application in the peri-operative period. The most prevalent side-effects of AEDs in neuro-oncology are cognitive dysfunction, bone marrow toxicity and skin hypersensitivity. Combining anti-epileptic drugs with chemotherapy, tyrosinekinase inhibitors or steroids increases the risks of drug-drug interactions. Plasma monitoring of AEDs for detecting drug insufficiency, interactions or toxicity helps in choosing the proper dose regimen. For practical use, tables on drug interactions between AEDs and cancer therapy are added together with a guideline on the medical management of seizure control including dose regimens.
Keywords: drug interactions